Implementation of Entrepreneurship Learning in Class IV SD Inpres Samata, Somba Opu Sub-District Gowa District - Iffah, Iffah; Devilla, Rego; Fahreza W, Muhammad (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the implementation process of entrepreneurship learning in class IV of SD Inpres Samata, Somba Opu District, Gowa Regency. This research is a qualitative study with a descriptive approach. The subjects in this study were supervisors, principals, 2 grade IV teachers, PAI teachers, PJOK teachers, and 2 grade IV students of SD Inpres Samata. Data collection techniques in this study used interviews, observation, and documentation while the data analysis techniques used included data reduction, data presentation, and conclusion drawing/verification. The results showed that entrepreneurship learning in class IV of SD Inpres Samata, Somba Opu District, Gowa Regency helped shape students' entrepreneurial character and skills, although its effectiveness varied. Teachers motivate students to be entrepreneurial with experiential learning methods and relevant case studies, raising their awareness early on. Interest in entrepreneurship grows through the manufacture and marketing of simple products. Creativity and innovation are developed through entrepreneurial projects, although there is limited use of technology. Challenge-based learning trains students to think critically and spot opportunities, but some still struggle to find independent solutions. Leadership is practiced through group work, but needs to be evaluated so that experience is evenly distributed. The courage to take risks is honed through small business simulations, although some students are still afraid of failure. Hard work is instilled through entrepreneurial tasks that foster perseverance and discipline, although further mentoring strategies are needed. Overall, this learning has a positive impact but still needs strengthening in mentoring, utilization of technology, and more complex challenges so that students are more independent and ready to face the business world.